2009
DOI: 10.17221/3/2009-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation results of new plum cultivars in a dense planting

Abstract: ABstrAct:Sixteen new plum cultivars mostly bred in Germany were tested together with several standards in a high density experimental orchard established at Holovousy in the spring of 2004 with spacing 5 × 1.5 m. Trees were trained as spindles on St. Julian A rootstock. In the orchard the following characteristics were evaluated: tree vigour based upon measuring of trunk-cross section area and canopy volume, yields, time of flowering, time of fruit ripening and basic parameters of fruit quality. The highest yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
12
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 10 publications
10
12
2
Order By: Relevance
“…Our YH for this cultivar was higher than those obtained by Meland (2005), but in the sixth year after planting. In general, our data for YT, YH and YE are similar to those published by Halapija-Kazija et al (2009) and with similar group of plum cultivars and inferior to the results obtained by Blažek and Pištěková (2009). Low values of YE and high TCSA values showed that Belošljiva rootstock in our study influenced relatively high vigour.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Our YH for this cultivar was higher than those obtained by Meland (2005), but in the sixth year after planting. In general, our data for YT, YH and YE are similar to those published by Halapija-Kazija et al (2009) and with similar group of plum cultivars and inferior to the results obtained by Blažek and Pištěková (2009). Low values of YE and high TCSA values showed that Belošljiva rootstock in our study influenced relatively high vigour.…”
Section: Resultssupporting
confidence: 85%
“…Mean FW and its variation recorded in this trial corresponded quite well to data observed in literature (Halapija-Kazija et al 2009). A greater disagreement in comparison to published data could be stated in BLU that should have possessed very large fruits, sometimes reaching weights up to 70 g (Blažek and Pištěková 2009). This result indicated that some plum cultivars on Belosljiva had the tendency to the decrease mean FW, particulary on sandy-loam soils, in accordance with the studies undertaken by Grzyb et al (1998).…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Pozna Plava stands out due to its late ripening time and long process of fruit ripening. Apart from the production purposes, this cultivar has a potential significance in the future projects of plum selection, since the ripening time is one of the well-known genotype-specific characteristics (García-Mariño et al 2008) and a long harvest period occurs as a result of a cultivar's specific ability to maintain the corresponding firmness of the flesh (Blažek, Pišteková 2009). Vol.…”
Section: Resultsmentioning
confidence: 99%
“…The 4 mid-to late-ripening cultivars we used, 'Stanley', 'Valor', 'President', and 'Marjorie's Seedling', are known to provide high yield (Agriculture and Horticulture Development Board, 2009;Blažek and Pištěková, 2009;Butac et al, 2012;Markuszewski and Kopytowski, 2013;Milosevic et al, 2010). Although the yield in Izumo was low for early-ripening cultivars ('Puchull', 'Purple Ais', and 'Blue Tan'), other countries reported high yields with early-ripening cultivars (Blažek and Pištěková, 2009;Embree et al, 1999).…”
Section: Suitable Cultivars For the Temperate Monsoon Climate Zone Bamentioning
confidence: 99%